Subthermocline anticyclonic gyre east of Mindanao and its relationship with the Mindanao Undercurrent - 宋丽娜;李元龙;刘传玉;王凡 (Chinese journal of oceanology and limnology, 2017)
The quasi-permanent anticyclonic gyre （ACG） east of Mindanao is a dominant feature of the subthermocline circulation in the southem Philippine Sea, and it is believed closely associated with the continuous northward alongshore flow of the Mindanao Undercurrent （MUC）. In this study, the structure and variability of this ACG were investigated using the 1950-2012 output of the Oceanic General Circulation Model for the Earth Simulator （OFES）, which can reproduce well the structure of the climatological intermediate-layer circulation and satellite-observed sea level variations in the southern Philippine Sea. Between 26.8-27.3 ao, the ACG covers a large area from the Mindanao coast to 131 ~E and from 3~N to 10~N. Its anticyclonic flow structure is unrelated to the surface Halmahera Eddy. The eddy-resolving simulation of the OFES revealed that the ACG consists of two components. The southern ACG （SACG） is centered at -6~N, while the northern ACG （NACG） is centered at -10~N. Seasonal and interannual variations of the ACG are linked to the variations of the northward MUC transport along the Mindanao coast, and the role of the SACG is more important than the NACG. Stronger （weaker） ACGs lead to greater （smaller） MUC transport. On the interannual timescale, the SACG shows a spectrum peak at 4-8 years, while the NACG has enhanced power within the 3-5-year band. A lead-lag correlation analysis indicates that interannual variations of the ACGs and the MUC transport are partly associated with the E1 Nifio-Southern Oscillation. Possible causes for the ACG variability are discussed.